Os institutos de participação popular na administração pública e suas delimitações - Dardani, Marina Centurion (2014)
The scope of this dissertation was the study of the institutions of popular participation in the Public Administration of binding and non-binding character and the possible difficulties faced by citizens to take an active and conscious participation. Sought to both the analysis of the legal nature of these participatory institutions, as well as an understanding of the constitutional design excused by law to the principle of popular participation. It was also amounted a theoretical study of the principle of subsidiarity, the participatory democracy and citizenship, for, after, entering the classification of participatory institutions and the constitutional and infra predictions governing the principles of participation and popular sovereignty. Entering the examination of each of the institutes, the theories that delimit the scope of these institutes and the margin of citizen influence in shaping the administrative decision were analyzed. It was tried to demonstrate that the opening of the Public Administration to citizen participation in administrative procedure makes the most legitimate administrative decision and allows that, before making the decision, plural opinions, which create dissention for, might be, after, taken into account to achieve consensus